Mothers’ Knowledge Regarding Infant Physical Needs - Alaa Issa Hamzah; Nehad Kadhim Hashim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Parents’ most important need was for accurate and honest information. Needs focused around sensitiveinfant care and involvement in decision-making. The greatest stressor for parents was alteration to theparental role, followed by infant appearance.A descriptive / Cross-sectional study design is carried to assessthe mothers’ knowledge regarding infant physical needs in Babylon governorate.The study conducted in Babylon Governorate in AL-Hashemia district, health centers. The sample size was(100) mother’s .The sample of study was multistage sampling, The data were collected through the trainingof two groups of specialized community health nursing student, each groups consisting of 2 students.They were trained on how to collect the sample and data collection method. The study used a developedquestionnaire (Arabic version( The data of the present study are analyzed through the use of StatisticalPackage of Social Sciences (SPSS) study concluded A third of the female participants in the study breastfeedtheir children through a bottle of milk and half of them feed their children 5 times a day, more than half ofthe participants had moderate information, while 40% of them had little information about caring for theirchildren physically. study recommended new mothers depend on the care of their children on the familyinheritance, especially the mother or older sister without adopting the scientific aspects and the developmentin the care of infants. Therefore, the study suggests developing an educational program that is part of themotherhood and childhood program.